Vitamin D deficiency is associated with inferior survival of patients with extranodal natural killer/T‐cell lymphoma. Issue 12 (28th November 2018) - Kim, Seok Jin; Shu, Cheng; Ryu, Kyung Ju; Kang, Danbee; Cho, Juhee; Ko, Young Hyeh; Lee, Soo‐Youn; Guallar, Eliseo; Zhao, Weili; Kim, Won Seog
Abstract : Vitamin D deficiency is a common health issue; however, the effect of vitamin D deficiency on the survival of T‐cell lymphoma is still not clear. We evaluated the impact of serum vitamin D level of patients with peripheral T‐cell lymphoma (PTCL) and extranodal natural killer/T‐cell lymphoma (ENKTL) on survival outcome. Pretreatment levels of 25‐hydroxyvitamin D [25(OH)D] and inflammatory cytokines were measured in serum samples that were archived at diagnosis, and we evaluated their association with survival in newly diagnosed patients with PTCL (n = 137) and ENKTL (n = 114) at a university‐based hospital in Korea. An independent cohort from Rui Jin Hospital (Shanghai, China) was used for validation. The median 25(OH)D serum level was 12.0 ng/mL (1.3‐60.0 ng/mL), and 40% had less than 10 ng/mL, which was defined as vitamin D deficiency. Median serum 25(OH)D levels were similar between PTCL (11.5 ng/mL) and ENKTL (12.9 ng/mL); however, vitamin D deficiency was associated with inferior survival in ENKTL but not with PTCL. The independent validation cohort (n = 115) also showed a significant association of vitamin D deficiency with poor survival in ENKTL. The 25(OH)D level had an inverse relation with inflammatory cytokines; this association had a negative effect only on survival of ENKTL, and not on PTCL. In conclusion, vitamin D deficiency was associated with inferior survival outcome of patients with ENKTL. Abstract : Vitamin D deficiency was associated with inferior survival of extranodal NK/T‐cell lymphoma but not with peripheral T‐cell lymphoma. Poor prognosis of vitamin D deficiency was related with increased inflammatory cytokines in extranodal NK/T‐cell lymphoma.